2019
DOI: 10.1155/2019/6128410
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Concentrations of Adropin, Afamin, and Neudesin in Children with Type 1 Diabetes

Abstract: Introduction The increasing knowledge of adropin, afamin, and neudesin and the regulation of glucose metabolism and insulin resistance allows for the assessment of the differences in their concentrations between the groups with varied duration of diabetes mellitus (DM). Aim of the Study Assessment of serum levels of adropin, afamin, and neudesin in children with type 1 diabetes, with respect to the disease duration. Materials and Methods The study consisted of 138 patients aged 5–18 years (M 40.58%). Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…Similarly, another study showed increased levels of adropin in kidneys and muscles in type 1 diabetic rats [29]. In contrast, a recent work found that adropin levels are downregulated in children who suffer from type 1 diabetes [30]. Therefore, studies testing the concentration of adropin in both types of diabetes provided partially contradictory data.…”
Section: Modulation Of Adropin By Body Mass Index (Bmi) Diet and DImentioning
confidence: 99%
“…Similarly, another study showed increased levels of adropin in kidneys and muscles in type 1 diabetic rats [29]. In contrast, a recent work found that adropin levels are downregulated in children who suffer from type 1 diabetes [30]. Therefore, studies testing the concentration of adropin in both types of diabetes provided partially contradictory data.…”
Section: Modulation Of Adropin By Body Mass Index (Bmi) Diet and DImentioning
confidence: 99%
“…According to the work of Ahmed et al, ADM2 is found to be preferentially up-regulated by bacteroides dorei (BD), which is a bacteria increased significantly at the time of onset of T1D. Enho is an energy homeostasis-associated gene that can produce a regulatory peptides named adropin, which has been identified to be strongly associated with type 1 diabetes in children ( Polkowska et al, 2019 ). FUT7 gene has been demonstrated to be linked with an antigen termed bile salt-dependent lipase which is reported to be associated with type 1 diabetes ( Panicot et al, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, afamin levels were significantly higher PCOS patients with IR compared to those without. Studies have shown that increased levels of afamin have been observed in patients with oxidative stress and inflammation [12][13][14][15]. A positive correlation between these two variables could be explained with the fact that inflammation and oxidative stress are common in PCOS patients with IR.…”
Section: Discussionmentioning
confidence: 98%
“…Studies show that Afamin increase is correlated with metabolic syndrome in PCOS patients [10][11][12]. Afamin was first identified in 1994 as the fourth member of the human albumin gene family, including vitamin D binding protein, alphafetoprotein, and human serum albumin [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation